Interrater reliability of the Saint-Anne Dargassies Scale in assessing the neurological patterns of healthy preterm newborns - Carla Ismirna Santos Alves; João Gonçalves de Medeiros; Luciana Arruda Carriço; Nívia Maria Arraes; Roselene Ferreira de Alencar; Aurea Nogueira de Melo
Abstract Objectives: to assess the interrater reliability of the Saint-Anne Dargassies Scale in assessing neurological patterns of healthy preterm newborns. Methods: twenty preterm newborns met the inclusion criteria for participation in this prospective study. The neurologic examination was performed using the Saint-Anne Dargassies Scale, showing normal serial cranial ultrasound examination. In order to test the reliability, the study was structured as follows: group I (rater 1/physiotherapist; rater 2/neonatologist); group II (rater 3/physiotherapist; rater 4/child neurologist) and the gold standard (expert and professor in pediatric neurology). Results: high interrater agreement was observed between groups I - II compared with the gold standard in assessing postural pattern (p<0.01). Regarding the assessment ofprimitive reflexes, greater agreement was observed in the evaluation of palmar grasp reflex and Moro reflex (p< 0.01) for group I compared with the gold standard. An analysis of tone demonstrated heterogeneous agreement, without compromising the reliability of the scale. The probability of equality between measurements of head circumference in the two groups, compared with the gold standard, was observed. Conclusions: the Saint-Anne Dargassies Scale demonstrated high reliability and homogeneity with significant power of reproducibility and may be capable to identify preterm newborns suspected of having neurological deficits.